Higher Education as a Factor of the Cities' Preservation in the Ural Macro-Region - Zborovsky, Garold Efimovich; Ambarova, Polina Anatolyevna (Economy of Regions, 2018)
The article considers the relationship between the development of Ural cities and institutions of higher education there. The topic of the study is relevant as there is a need to find resources for socio-economic, demographic, and sociocultural development of the medium-sized, big and large cities of the Ural Federal District (UFD). Many of these cities have been under the crisis. In our view, one of the ways to overcome it is to develop there the universities and branches of higher education institutions. We focus on the relationships and dependencies between contradictory processes in higher education and constructive and destructive trends of the dynamics of the Ural cities. For the first time, on the theoretical level and empirical data, we show the conditions and limitations for the city-preserving function of universities. This function is closely connected with the «third mission» of the university. We prove that under conditions of social and economic uncertainty, the universities and strong branches of universities can be the key factor in preserving middle-sized, big and large cities. With the results of the case studies of three UFD cities - Nizhny Tagil, Surgut, Tobolsk, we show the necessity of feedback between the city and the university. The study of higher education in these cities confirmed the connection between the degradation of educational institutions and recent negative trends - youth migration, and then - social and economic decline of the city. We have argued the need for mutual support of educational institutions and urban actors. The city-preserving function of universities can be implemented under the condition of the university-preserving activities of university management, urban community, urban and the regional authorities. In our opinion, the strategies of cities should include provisions on the universities' preservation and interaction with them as with mechanisms enabling cities to act as the main agents of socio-economic and socio-cultural development of the Ural Federal District. The results of the research can become a basis for the improvement of UFD educational policy as well as for the development of strategies for medium-sized, big and large cities of the region